An updated Checklist of the Myospila Rondani (Diptera: Muscidae) of India with description of a new species - Jana, Nandan; Hazari, Pravas; Sinha, Shuvra Kanti; Wei, Lianmeng (Zootaxa, 2023)
A list of 19 species of the genus Myospila Rondani, 1856 (Diptera, Muscidae) from India is prepared based on our collection and available literature. The study documented a new species, Myospila himalayensis Jana, Hazari & Sinha, sp. nov., from Darjeeling, West Bengal, India. A description of the new species is provided, along with male terminalia figured and described. Taxonomic notes on the closely related species are also illustrated.